Gestión de la capacitación y desarrollo de competencias del personal de enfermería del Hospital II-1 Contamana 2023 - Angaspilco Rodriguez, Erminia Maricruz (2025)
This study investigated the relationship between training management and competency development of nursing staff at Hospital II-1 Contamana in 2023. A correlational descriptive research was adopted with a non-experimental design. With a sample of 180 people, 85 men and 95 women, a questionnaire was used as a data collection instrument. After analyzing the results, it was found that only 27% of employees rate the training as regular, while others consider that it is sometimes carried out by untrained planners. In addition, 27% indicated that the importance of training is not always promoted on a consistent basis. 25% say that training needs are not always adequately diagnosed for feedback. In relation to the development of competencies, another 27% qualify it as regular, and recognize that sometimes it is not reflected in their professional performance. 30% consider that supervision only corrects and does not guide. On the other hand, 24% say that supervision can motivate and reinforce. A positive and significant relationship was evidenced between the management of training and the development of competencies of the nursing staff of the Hospital II-1 of Contamana, with a correlation coefficient of 0.821 and a significance value of 0.000.